The Effectiveness of Using Honey in Feed for Fish Sex Change Sword Plate (Xiphophorus helleri) - Mustaqim Mustaqim; Wenny Novita Sari; Jumadi (Warmadewa University Press, 2023)
This study aims to determine the effect of forest bee honey on changes in male sex of sword platy fish (Xiphophorus helleri). The benefits of this study were to determine the appropriate dose of honey for changes in male sex and how the survival rate of sword platy fish larvae was. This study was conducted using a completely randomized design (CRD) with five treatments and three replications, namely Treatment A: Control (Ordinary Feed), Treatment B: Dosage of 3 ml of honey mixed into 100 g of feed, Treatment C: Dosage of 4 ml of honey which is mixed into 100 g of feed, Treatment D : Dosage of 5 ml of honey mixed into 100 g of feed, Treatment E : Dose of 6 ml of honey mixed into 100 g of feed. The results showed that mixing honey into feed gave a significantly different effect on the percentage of male sex ratio where Fcount > Ftable (5.15 > 3.48). Where the best dose is found in treatment E: 6 ml of honey mixed into 100 g of feed with a percentage of 66.05%. While the lowest percentage value is in treatment A (Control) with a total percentage of 40.79%. For the survival rate, mixing honey into the feed had no effect between all treatments. The percentage of survival rates is still in the range above 50%. The range of water quality values ​​is the temperature ranges from 26.55-27.52 0C, pH ranges from 7.02-7.06 and dissolved oxygen ranges from 5.13-5.31 ppm.